Personal Branding Gus Miftah di TikTok @gusmiftah99 melalui Eight Laws of Personal Branding (Analisis Konten Januari 2024 -Februari 2026) - Moch. Raja Nata Akhira; Saifudin Zuhri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the personal branding of Miftah Maulana Habiburrahman through the TikTok account @gusmiftah99 using the perspective of the Eight Laws of Personal Branding proposed by Peter Montoya. The research applies a descriptive qualitative approach with content analysis techniques to examine selected posts published between January 2024 and February 2026. The units of analysis include visual elements, spoken narratives, and captions that represent how self-image is constructed and communicated to audiences in the digital space. The findings reveal that personal branding is predominantly shaped by four major aspects. First, a humanistic and communicative Islamic preaching specialization grounded in Qur’anic and hadith references strengthens credibility and authority. Second, leadership is demonstrated through responses to social issues and public controversies, reflecting responsibility and religious guidance. Third, distinctiveness is reinforced through unique visual style and the choice of unconventional preaching venues, which differentiate the figure from other preachers. Fourth, consistent content production and visible social actions enhance digital visibility and foster public trust. The alignment between conveyed messages and real-life actions further supports a perception of integrity and social concern. Overall, the study indicates that the personal branding of a religious figure on social media is dynamically constructed through the interaction of values, communication strategies, content consistency, and audience engagement in the contemporary digital environment.